Overview of Simulation in Wood Plastic Composites Manufacturing - Gupta, Ritu; Noraziah, Ahmad; Gupta, Arun; Abdalla, Ahmed N. (Informatics Publishing Limited, 2017)
This paper presents a review on the application of simulation software as a tool aiding in design and manufacturing aspect of wood plastic composites (WPCs). The scope of application of models present in literature by previous researchers is discussed in general. Methods/Statistical Analysis: A review on the simulation in wood plastic composites manufactured by compression moulding process is presented by analyzing the data present in literature. Important factors which affect the mechanical properties of final wood plastic composite products are stated. This paper also addresses the challenges of application of simulation models for prediction of mechanical properties of wood plastic composites by other researchers. Findings: Simulation models related to wood based composites are discussed and their applicability for wood plastic composites is reported. A need of simulation software for WPC prediction purpose and easy to use by other researchers is highlighted. Application/Improvements: Importance of collaborative efforts between material researchers and computer science researchers is also highlighted to fulfill the need of the simulation software in wood plastic composite area.